Research on Key Technologies of Unified Operation Oriented Fixed-Mobile-Convergence Smart Pipe - Jing Han; Yasong Wang; Xin Sun; Jianquan Wang (Dianxin kexue)
In order to meet the convergence needs of fixed smart pipe and mobile smart pipe，the unified operation oriented fixed-mobile-convergence smart pipe architecture was proposed firstly. Then the evolution of fixed-mobile-convergence smart pipe was analyzed. Finally，key technologies related were described in detail，containing convergence in network capability open platform layer，convergence in control layer，convergence in network layer，convergence of billing，and dynamic policy controlling.